Comportamento do vento e aproveitamento eólico na região central de Alagoas (Craíbas) - Cruz, Nareida Simone Delgado da (2017)
The aims of this work is to study the behavior of the wind and its peculiarities in Craíbas – AL (09° 40' 03.4" S 36° 50' 40.2" W, 210m) and to analyze the viability of place in terms of wind energy resource. For this purpose, data from the Wind Forecasting Project for Wind Farms in Northeast Brazil (PVPN) were used. The study area is inserted in rural zone of the municipality of Craíbas - AL located in the central region of the state of Alagoas. A climatological analysis was performed by monthly means of meteorological variables (temperature, relative humidity, pressure, velocity, direction, and precipitation). The hypothesis of using Meteorological stations data in the wind energy study was tested. The atmospheric stability conditions were analyzed by Richardson number (Ri) and Pasquill-Gifford-Turner classification. The gusts records were used in three levels (100, 70 and 50m) as parameters to analyze the flow regularity. Then, it was made an investigation of the influence of gusts in nearby regions. Finally, an analysis of site suitability for wind energy was made using the WASP (Wind Atlas, Analysis and Application Program). The results showed that at a height of 100 m the average monthly speed varies about 6.73 m/s between the minimum (May) and the maximum (October). The average annual velocity was 5.87 m/s at 50 m, 6.25 m/s at 70 m. The diurnal cycle is marked by an increase during afternoon with a maximum at the beginning of night. The wind direction varied little throughout the year with SE as the predominant direction. The use of Meteorological stations data supports the present study was not a viable option. The atmosphere was predominantly unstable throughout the year (49%) and 31% of the cases were stable and 20% neutral. Regarding the hourly, it was predominantly unstable during the day (65.8%) and stable at night (35.3%). The occurrence of gust has no connection with those identified in the Meteorological stations that are being conditioned only under the conditions of stability. Regarding the Weibull parameters, the period of study showed an average speed of 6.72 m/s, "k" equal to 3.45 and "A" equal to 7.5 m/s. It has been proven that both Craíbas and the surrounding region is viable to exploit the wind resource. It has also been proven that in Craíbas specifically this exploration can be done at heights less than 100m making the installation of a wind farm economically viable.